The International Evolution of Mediation: A Call for Dialogue and Deliberation - Stipanowich, Thomas J (Victoria University of Wellington Law Review, 2015)
The following article is a revised and expanded version of lectures delivered by the author at the Victoria University of Wellington School of Law and the Faculty of Law, University of Auckland in October, 2014 as the New Zealand Law Foundation's International Dispute Resolution Visiting Scholar. The author posits that the mounting global preoccupation with mediation, resulting in a proliferating array of institutions, programmes, laws and regulations; an international "evangelical" movement; and growing impetus for an international convention promoting the recognition and enforcement of mediated settlement agreements, should be accompanied by our collective reflection, dialogue and discernment regarding where we have come to and where we are going. He urges active discussion and deliberation on a host of questions and concerns, including (1) our fundamental understanding of the nature and practice of mediation; (2) the impact of lawyers on mediation, and the appropriate interplay between client and counsel in making process choices; (3) the influence of culture and of legal traditions; (4) the interplay between the facilitation of settlement and processes of adjudication; (5) the potential impact of mediation on the rendition of justice. This conversation should be augmented by an assessment of current mega-trends – the challenges and opportunities presented by information technology, neuropsychology, the mining of big data, and initiatives aimed at institutionalising or professionalising mediation. Finally, there should be a new examination of heretofore-unfulfilled opportunities, such as the "upstream" (that is, early and pre-litigation) use of skills and insights gleaned from our experience with mediation for the purpose of sustaining and improving relationships.